2022
DOI: 10.3390/molecules27103268
|View full text |Cite
|
Sign up to set email alerts
|

Study on Supramolecules in Traditional Chinese Medicine Decoction

Abstract: With the application of the concept of supramolecular chemistry to various fields, a large number of supramolecules have been discovered. The chemical components of traditional Chinese medicine have various sources and unique structures. During the high-temperature boiling process, various active components form supramolecules due to complex interactions. The supramolecular structure in a traditional Chinese medicine decoction can not only be used as a drug carrier to promote the absorption and distribution of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…The names, molecular formulae, and accurate mass of all pesticides were loaded into the MassHunter Personal Compound Database and Library (PCDL) management soware to establish the primary accurate data database of 255 pesticides. The LC-Q-TOF/MS conducted secondary scanning in targeted MS/MS mode, inputted the accurate mass of the precursor ions, retention time, and four different collision energies (10,20,30, and 40 eV) collected by primary mass spectrometry, collected the fragment ion mass spectrogram of precursor ions of each pesticide at different collision energies, and imported them into PCDL soware to establish a secondary accurate mass database and spectral library of 255 pesticides.…”
Section: Construction Of An Accurate Quality Databasementioning
confidence: 99%
See 1 more Smart Citation
“…The names, molecular formulae, and accurate mass of all pesticides were loaded into the MassHunter Personal Compound Database and Library (PCDL) management soware to establish the primary accurate data database of 255 pesticides. The LC-Q-TOF/MS conducted secondary scanning in targeted MS/MS mode, inputted the accurate mass of the precursor ions, retention time, and four different collision energies (10,20,30, and 40 eV) collected by primary mass spectrometry, collected the fragment ion mass spectrogram of precursor ions of each pesticide at different collision energies, and imported them into PCDL soware to establish a secondary accurate mass database and spectral library of 255 pesticides.…”
Section: Construction Of An Accurate Quality Databasementioning
confidence: 99%
“…Owing to its rapid absorption, distribution, effectiveness, and versatility, it accounts for 80% of all ancient classical prescriptions of TCM. [10][11][12][13] Therefore, it is of utmost importance to undertake a comprehensive study on safety evaluation and quality control of the entire process, from raw materials to nal preparations of TCM. Currently, the majority of research has focused on detection methods for pesticide residues in Chinese herbal pieces, including QuEChERS, [14][15][16][17] dispersed liquid-liquid microextraction, 18,19 matrix dispersed solid-phase extraction, 16 and gel permeation chromatography, 20 whereas there are few studies on those of pesticide residues in Chinese herbal decoction.…”
Section: Introductionmentioning
confidence: 99%
“…In traditional Chinese medicine (TCM), decoctions have long been widely used and are the most frequently employed form of medication . Recently, researchers have discovered the presence of nanoaggregates in TCM decoctions, offering a new perspective on the scientific connotation of traditional treatments. These nanoparticles have been identified in various decoctions, including Ge-Gen-Qin-Lian-Tang, Huang-Lian-Jie-Du-Tang, and Nao-Luo-Xin-Tong-Tang . Self-assembled submicrometer particles constructed by berberine and curcumin through noncovalent bonding significantly enhance antimicrobial activity .…”
Section: Introductionmentioning
confidence: 99%
“…The resulting data also indicated that aggregates and precipitates in herbal decoctions should be carefully handled in production and pharmacological research. In addition, nanoparticles discovered in Huanglian Jiedu , Huanglian , Maxing Shigan , Baihu , Liujunzi , and Shaoyao Gancao decoctions showed superior properties and activities. ,, Even in Turkish gall extracts, researchers found the presence of spherical nanoparticles that possessed the ideal size, strong antioxidant activity in scavenging various radicals, and antibacterial performance . However, whether nanoparticles exist in the AM–AS codecoction remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…As this concept gradually became well-known, researchers discovered many supramolecules in soups, such as fish soup, freshwater clam soup, and pork bone soup . Decocting is not a single process of extracting components from hot water, which drives the components to spontaneously form supramolecular aggregates with a certain particle size . The processing of food soups is similar to that of herb decoctions.…”
Section: Introductionmentioning
confidence: 99%